Technological model of building life cycle/Statinio gyvavimo ciklo technologinis modelis - Martinaitis, Vytautas; Rogoža, Artūras (Journal of Civil Engineering and Management, 2001)
Under present conditions there are no regulating documents for building life span, maintenance, recondition and reconstruction works and periodicity in Lithuania. The suggested model allows to evaluate optimal values for building work periodicity. The purpose of the model is to calculate the depreciable value of compound construction (building) at every moment of its life cycle. There can be determined by this model the relations between building depreciable value and its components reconstruction character. The function mode of components deterioration can be changed with technology progress. It can be controlled by single coefficients in model. Single components reconstruction affects not only building aesthetic conditions, but also operating costs (energy consumption, amount of renovation work), which could be linked with elements deterioration. This model is called technological model, and it does not include cash expenditure calculations for work, materials and energy, but it is a basis for further economical modelling of building life cycle.Article in Lithuanian.First Published Online: 30 Jul 2012